Analisis Ekonomi Politik Neoklasik Terhadap Etika Kebijakan di Indonesia - Nadiah Miftahul Rohmah; Eli Apud Saepudin; Alya Rahmah; Aliyah; M Raden Massyahid; Galang Yudistias (UNIVERSITAS SERAMBI MEKKAH, 2024)
Neoclassical political economy is a school of thought that combines neoclassical economic theory with political analysis. It focuses on how political institutions and the distribution of power affect economic performance. Role of the State: The role of the state in neoclassical political economy is limited to providing basic infrastructure, law enforcement, and security. State intervention in the market is considered to interfere with market mechanisms and hinder efficiency. Rational Choice: Individuals are assumed to be rational agents who act based on their self-interest. These individual choices, in their interactions in the market, will result in market equilibrium. result in market equilibrium. Wealth Distribution: Neoclassical political economy assumes that the existing distribution of wealth is the result of individual choice and hard work.